Hingabe wagen - barmherzig handeln: eine Antwort auf die Vulnerabilität der Anderen - Keul, Hildegund (Zeitschrift für katholische Theologie, 2016)
The article relates the concept of mercy to the discourse on vulnerability. It suggests that despite the common perception of vulnerability as something to be avoided merciful actions in fact exposes oneself to being vulnerable in order to attend to the vulnerability of others. Various examples of both individual and sociopolitical actions serve to illustrate this point. Finally the article suggests that the theological contribution to the discourse on mercy and vulnerability would be the attention given to the realization that within vulnerability there are creative powers which are given expression in mercy.